(untitled) (European Journal of Marketing and Economics, 2020)
The present work seeks to analyze and contrast the previous characteristics of the general financial situation of the main Mexican airlines. This is especially relevant, since in general there were problems in leverage and profitability in some of them, since exercises prior to 2020. In this sense, it is important to clarify the conditions in which several surgical surgeries were developed, faced by economic and health crisis of the first decade of this century and finally, they will face this global phenomenon unprecedented in the economic history of this century and much of the previous one. In the part of presenting the figures of reduction in passenger flows today, the characteristics and problems they have faced, as well as some reflections on how they can be better rid. Likewise, a model is presented that emphasizes the change in Aeroméxico’s financial situation, towards a critical state in terms of the fall in the activity of commercial aviation worldwide. Finally, there are some reflections and recommendations regarding the possible alternatives for this important sector of the Mexican economy, in general, Aeroméxico in particular, can get out of this difficult and complex current environment.